Determining Factors that Influence Heart Hate Recovery (HRR) Result on Treadmill Stress Test - F Rahman (ACI (Acta Cardiologia Indonesiana), 2017)
Introduction: Stress exercise electrocardiogram is a valid diagnostic and prognostic tool for .....